Debt conversion in principle and practice - BIRD, G. (PSL Quarterly Review, 2013)
There is increasing interest in the restructuring of the international debt of developing countries by converting the debt into equity. Such schemes have recently been introduced in a number of countries, mainly in South America, although their impact has so far been marginal. The author considers the theory and mechanisms of debt conversion and assesses some of the advantages and problems involved. In a final part of the paper, some examples of debt conversion in practice are discussed. These include Argentina, the Philippines, Mexico, Brazil and Chile. JEL: F34, F63